SYSTEMATIZATION OF THE STRATEGIC CHARACTERISTICS OF THE ENTERPRISES IN THEIR ACCOUNTING AND ANALYTICAL SYSTEM - Natalia Yurievna Orlyuk; Zoya Fedorovna Nalimova (Современная наука и инновации, 2022)
Consideration of the components forming the accounting and analytical system of strategic indicators of economic activity relative to the data obtained from the continuous implementation of financial and tax accounting, based on the strategic indicators is a critical element of uniform evaluation the performance of the company.